The prevalence of phenylketonuria among children with mental retardation in Kelantan - Omar, Julia (2001)
The prevalence of phenylketonuria (PKU) in Malaysia to date is not known since no study has been conducted to address the subject. The objectives of this study were to determine the prevalence of PKU among the mentally retarded children in Kelantan, to determine the feasibility of carrying out a screening programme for PKU in newborns and to establish a method for PKU screening should the need arise later on. The study was a cross-sectional survey involving all the schools with special programmes for mentally retarded children and community- and clinic-based rehabilitation centers ( CCRC) in Kelantan. All children listed and attended these two institutions were taken as the study samples. A validated questionnaire was used to obtain personal and socioeconomic information of the patients and their families. The questionnaire was collected together with the written consent for the study before the final list of respondents was recorded. Blood spots on filter papers were collected by a finger prick method using automated disposable lancet. Validation of the information in the questionnaire, physical examinations and blood spots collection were done at the respective schools and CCRC. Phenylalanine assays were done using the Bacteria Inhibition Assay (BIA), also known as the Guthrie method.